A General Template‐Induced Sulfuration Approach for Preparing Bifunctional Hollow Sulfides for High‐Performance Al‐ and Li‐ion Batteries. Issue 2 (10th December 2020) - Liu, Jinyun; Zhang, Min; Han, Tianli; Si, Ting; Zhang, Huigang; Hu, Chaoquan
Abstract : Hollow nanomaterials have attracted broad attention due to their geometric configuration with some special properties such as fast ion diffusion, and accommodating structural transformation. However, conventional approaches for preparing hollow nanostructure commonly need an additional template removal process, which is time‐consuming and may require some corrosive chemicals. Herein, a general template‐induced sulfuration method is presented which is applicable for preparing a broad set of hollow sulfides. Sulfur particles are synthesized, which are then used as both template and sulfurizing reagent. During the heating, the template is removed along with the sublimation of sulfur, meanwhile the sulfur vapors sulfurize the coated precursor, finally forming a hollow sulfide nanostructure. As a demonstrating case study, a hollow NiS2 nanostructure is prepared through the presented approach which is confirmed extendable for many other sulfides such as CoS2, Bi2 S3, and Cu2 S. Furthermore, the hollow NiS2 exhibits bifunctional properties using as Al‐ion battery cathode and Li‐ion battery anode with good electrochemical performance, such as a 1000‐cycles stable capacity at high current density of 5 A g −1, stable temperature‐endurable property, and well‐recoverable rate performance. Abstract : A general template‐induced sulfuration method which is applicable for preparing a broad set of hollow sulfides is developed. As a demonstrating study, a hollow nickel disulfide is prepared which has been confirmed extendable for other sulfides. The nickel disulfide exhibits bifunctional properties using as aluminum‐ion battery cathode and lithium‐ion battery anode with good electrochemical performances.